Optimization-based locomotion planning, estimation, and control design for the atlas humanoid robot - Kuindersma, Scott; Deits, Robin; Fallon, Maurice; Valenzuela, Andrés; Dai, Hongkai; Permenter, Frank; Koolen, Twan; Marion, Pat; Tedrake, Russ (Autonomous robots, 2016)
This paper describes a collection of optimization algorithms for achieving dynamic planning, control, and state estimation for a bipedal robot designed to operate reliably in complex environments. To make challenging locomotion tasks tractable, we describe several novel applications of convex, mixed-integer, and sparse nonlinear optimization to problems ranging from footstep placement to whole-body planning and control. We also present a state estimator formulation that, when combined with our walking controller, permits highly precise execution of extended walking plans over non-flat terrain. We describe our complete system integration and experiments carried out on Atlas, a full-size hydraulic humanoid robot built by Boston Dynamics, Inc.